Analisis Structural Equation Modeling (SEM) Pengaruh Transformational Leadership Terhadap Employee Performance - Sari, Citra Arum; Nugroho, Sukmo Hadi (Rekayasa, 2024)
Performance results in a company can increase due to the influence of the transformational leadership style supported by how job satisfaction and behavior of its employees. Job satisfaction and OCB function to have a positive impact on employee performance, if employees are satisfied with what is given by their leaders, it will affect the progress of the company and feel encouraged to work better as well as the impact of OCB and transformational leadership on them, in terms of involving employees in voluntary work which ultimately improves performance. Contributions to this research so that in the future it can expand information and new references. This research also expands the literature by examining the mediating influence of OCB and provides new directions for researchers to study transformational leadership and OCB. The sampling method is purposive. The data collection technique begins with the distribution of an initial questionnaire (pre test) to 30 respondents, then continues with a sample of 150 respondents. The research was conducted quantitatively with the SEM (Structural Equation Model) Lisrel method. The results showed that transformational leadership has a positive effect on job satisfaction, organizational citizenship behavior and employee performance directly and job satisfaction and OCB have a positive effect indirectly.